ANO7 is associated with aggressive prostate cancer. Issue 10 (22nd September 2018) - Kaikkonen, Elina; Rantapero, Tommi; Zhang, Qin; Taimen, Pekka; Laitinen, Virpi; Kallajoki, Markku; Jambulingam, Dhanaprakash; Ettala, Otto; Knaapila, Juha; Boström, Peter J.; Wahlström, Gudrun; Sipeky, Csilla; et al.
Abstract : Prostate cancer is one of the most common and heritable human cancers. Our aim was to find germline biomarkers that can predict disease outcome. We previously detected predisposing signals at 2q37, the location of the prostate specific ANO7 gene. To investigate, in detail, the associations between the ANO7 gene and PrCa risk and disease aggressiveness, ANO7 was sequenced in castration resistant tumors together with samples from unselected PrCa patients and unaffected males. Two pathogenic variants were discovered and genotyped in 1769 patients and 1711 unaffected males. Expression of ANO7 vs. PrCa aggressiveness was investigated. Different databases along with Swedish and Norwegian cohorts were used for validation. Case–control and aggressive vs. nonaggressive association analyses were performed against risk and/or cancer aggressiveness. The ANO7 mRNA level and patient survival were analyzed using expression data from databases. Variant rs77559646 showed both risk (OR 1.40; p = 0.009, 95% CI 1.09–1.78) and association with aggressive PrCa (Genotype test p = 0.04). It was found to be an eQTL for ANO7 (Linear model p ‐values for Finnish patients p = 0.009; Camcap prostate tumor p = 2.53E‐06; Stockholm prostate tumor cohort p = 1.53E‐13). rs148609049 was not associated with risk, but was related to shorter survival (HR 1.56; 95% CI 1.03–2.36). High ANO7 expression was independently linked to poor survival (HR 18.4; 95% CI 1.43–237). ANO7 genotypes correlate with expression and biochemical relapse, suggesting that ANO7 is a potential PrCa susceptibility gene and that its elevated expression correlates with disease severity and outcome. Abstract : What's new? The discovery of germline biomarkers to predict outcome in prostate cancer could greatly aid disease management. One such marker of particular interest in this regard is the prostate‐specific gene ANO7, which previous studies have associated with high‐grade prostate cancer. Here, specific germline ANO7 genotypes were associated with increased prostate cancer risk. In patients, ANO7 expression correlated with disease severity, with elevated expression associated with decreased overall survival. The data suggest that ANO7 is a susceptibility marker in prostate cancer and, with further characterization, could be used to inform patient selection strategies and therapeutic approaches.